IMPLEMENTASI KEBIJAKAN PENGELOLAAN OBJEK PARIWISATA ALAM PANTAI KOMBI DI KABUPATEN MINAHASA PROVINSI SULAWESI UTARA - TANOD, LITHA MARIA; AREROS, WILLIAM; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2020)
Minahasa regency has natural potential that can be developed to support the tourism sector. The beach inKombi sub-district is one of the natural potentials that is currently one of the alternati people traveling. Thisresearch was conducted to analyze the implementation of natural tourism object management policy ofKombi Beach in Minahasa Regency of North Sulawesi Province in the development of developmentresources studies especially the concept of policy implementation.This research uses qualitative design. Data is collected through interviews, observations and documentationstudies. The informants in this study were the head of the Tourism and Culture Office of Minahasa Regency,the Head of Kombi District, the owner and manager of tourist attractions and visitors. The focus of theresearch is on the size and objectives of policies, resources, characteristics of implementing agents, attitudesor tendencies of the executives, communication between organizations and implementing activities as wellas the economic and social environment. Data analysis is done through data categorization, data reduction,data interpretation and conclusion drawing.Research findings that the Tourism and Culture Office of Minahasa Regency does not yet have a policy thatbecomes a clear legal basis in the development of tourism object management in Kombi Beach. Humanresources management of tourist attractions owned by the village does not have good ability and has notbeen supported by the availability of supporting facilities and budget for the management of touristattractions to be better. This situation is different from the management of privately owned tourist attractionsthat have professional human resources, better tourist facilities and professional budget management. Theorganizational structure of the well-organized Tourism and Culture Office of Minahasa Regency has notbeen able to formulate and program development that supports the management of kombi beach naturalattractions as one of the promising natural tourist destinations as a result of the current regional planningand budgeting system. The open attitude shown by the head of the Tourism and Culture Office of MinahasaRegency to give authority to the village owners of tourist attractions in the management of the tourismvillage model has not been a program of the Minahasa Regency Government. Communication between theTourism and Culture Office of South Minahasa Regency and the owner of tourist attractions in KombiBeach in the management and development of tourist attractions has not gone well. The people aroundKombi beach tourism object have not made the tourism sector as a profession to support the family economybecause tourist visits have not periodically occurred every day.Keywords: Policy Implementation; Management; Tourism